Design of a portable control platform for Rod-Driven continuum parallel robots (2024)
This project aimed to design and implement a portable, modular, and scalable platform in conjunction with a control system tailored for rod-driven continuum parallel robots. The primary objective was to develop a versatile mounting solution that would facilitate efficient robot movement across diverse applications. The project involved the design and construction of the mounting platform, as well as the development of the control interface. A rod-driven continuum parallel robot was designed and implemented, with a focus on miniaturization and enhancement of the structure. Furthermore, the project aimed to implement a customized language specification for programming the linear actuators, enabling tailored control and operational flexibility. Additionally, an application was developed to interface with the control system, utilizing the created protocol to ensure seamless communication and precise control.